Electrochemical growth of polyaniline films controlled with light - Ashleigh K. Wilson; Chantel Johnson; Jaycie Jenkins; Asia Jones; Natalia Noginova (Electrochemistry Communications)
Plasmonic environment and light illumination can have significant impacts on electrochemical reactions. We explore the possibility to control electrochemical deposition of polyaniline films on gold substrates with light and study factors affecting film growth. The analysis of light-induced patterns in films exposed to laser light at different intensities and wavelengths reveals that the growth rate increases the light intensity at small intensities and then saturates with the further increase in laser light intensity. The wavelength of illumination does not significantly affect the results. The findings provide opportunities in fabrication of plasmonic structures with specific patterns of electrochromic polymer, which can operate as electrically tunable metasurfaces and plasmonic systems.